Modification of nickel ferrite nanoparticles by sodium docusate surfactant for superior crystal violet dye removal from aqueous solutions - Nada S. Al-Kadhi; Ghadah M. Al-Senani; Fawaz A. Saad; Alaa M. Munshi; Ehab A. Abdelrahman (Scientific Reports)
Abstract In this study, nickel ferrite (NiFe2O4) nanoparticles were synthesized using the Pechini sol-gel method and modified with sodium docusate surfactant. The modified nanoparticles showed an enhanced adsorption capacity of 384.62 mg/g for crystal violet dye, compared to 237.53 mg/g for unmodified NiFe2O4. Characterization was performed using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), energy-dispersive X-ray spectroscopy (EDX), and scanning electron microscopy (SEM) techniques. The adsorption process was spontaneous, exothermic, and followed the Langmuir isotherm and pseudo-second-order kinetic model. Optimal conditions for maximum dye removal were achieved at pH 10, 50 min, and 298 K. Additionally, the synthesized adsorbents demonstrated excellent regeneration and reusability over five adsorption-desorption cycles with minimal efficiency loss.